DESIGN AND IMPLEMENTATION OF AUTOMATIC SLUDGE PUMPING SYSTEM USING SUBMERSIBLE PUMP AND STRAINER WITH FLOAT LEVEL SWITCH OIL IN CARRIGE TIPPLER TRANSFER POND IN SEMILAR PALM OIL FACTORY - Daniel Joshua Batubara; Deni Rachmat (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
In the wastewater management process at Semilar Palm Oil Mill, sludge accumulation in the carriage tippler transfer pit often obstructs flow to subsequent treatment units. To address this issue, an automatic sludge pumping system was designed and implemented using a submersible pump, strainer, and float level switch. This system is engineered to operate automatically based on sludge level, eliminating the need for manual operation by workers. The design involved selecting a submersible pump suitable for sludge characteristics and required flow rate, installing a strainer to prevent large solid particles from entering and clogging the pump, and using a float level switch with dual-point control (high and low levels) to automate the pump's start-stop cycle. The system was installed directly in the transfer pit and calibrated for stable performance in a muddy and corrosive environment. Implementation results show that the system significantly reduced the pit drainage time and minimized downtime due to clogging. During the trial period, the system operated reliably, responded effectively to sludge level changes, and improved operational efficiency by reducing manual intervention. This system provides a reliable and practical solution for sludge handling in palm oil mills while supporting more efficient and environmentally friendly waste management practices.